EANM procedure guidelines for brain PET imaging using [18F]FDG, version 3 - Guedj, Eric; Varrone, Andrea; Boellaard, Ronald; Albert, Nathalie L.; Barthel, Henryk; van Berckel, Bart; Brendel, Matthias; Cecchin, Diego; Ekmekcioglu, Ozgul; Garibotto, Valentina; Lammertsma, Adriaan A.; Law, Ian; et al. (European journal of nuclear medicine and molecular imaging, 2022)
The present procedural guidelines summarize the current views of the EANM Neuro-Imaging Committee (NIC). The purpose of these guidelines is to assist nuclear medicine practitioners in making recommendations, performing, interpreting, and reporting results of [ 18 F]FDG-PET imaging of the brain. The aim is to help achieve a high-quality standard of [ 18 F]FDG brain imaging and to further increase the diagnostic impact of this technique in neurological, neurosurgical, and psychiatric practice. The present document replaces a former version of the guidelines that have been published in 2009. These new guidelines include an update in the light of advances in PET technology such as the introduction of digital PET and hybrid PET/MR systems, advances in individual PET semiquantitative analysis, and current broadening clinical indications (e.g., for encephalitis and brain lymphoma). Further insight has also become available about hyperglycemia effects in patients who undergo brain [ 18 F]FDG-PET. Accordingly, the patient preparation procedure has been updated. Finally, most typical brain patterns of metabolic changes are summarized for neurodegenerative diseases. The present guidelines are specifically intended to present information related to the European practice. The information provided should be taken in the context of local conditions and regulations.